Atypical Presentation of Obsessive–Compulsive Disorder – Utilization of Technology for Yielding to Ego-dystonic Thoughts - Bhavik Tushar Chheda; Anup S. Bharati (Annals of Indian Psychiatry)
Obsessive–compulsive disorder (OCD) is a common psychiatric disorder which is easily recognized. However, sometimes patients of OCD present in such an atypical or bizarre way that their problem comes to notice as being a psychiatric disorder after multiple consultations in different specialties. We report a case of a man who had started recording his own conversations with people, pertaining to the thought that he might say something bad about his family and disgrace them. He could be diagnosed as a case of OCD after meticulous evaluation and studying his response to treatment. There was a significant improvement in all the presenting symptoms over a period of 6 weeks on 40 mg of fluoxetine.